Visual impairment and blindness in Alkharj, Saudi Arabia - Bahakim, Nasraddin; Geddawy, Ayman; Aldarrab, Abdulrahman; Mansour Mohammad Alajmi; Alsaidan, Mohammed; Aljuhani, Maher; Hussain, Abdulqayyum; Alqahtani, Abdulhakim; Alshaikhi, Abdulmajeed; Al-Ghamdi, Sameer (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the incidence and causes of visual impairment and blindness among patients attending eye clinics in a tertiary care setting. Method: The retrospective study was conducted in Alkharj city, Saudi Arabia, from May to November 2022, and comprised records of patients who visited eye clinics of two main hospitals in the city with complaints of low vision or blindness between January 2021 and December 2021. Medical history, family history and ophthalmological examination results of each patient were reviewed, and the causes and frequency of occurrence of visual impairment and blindness were determined. Data was analysed using SPSS 21. Results: Of the 433 patients, 269(62.1%) were female and 164(37.9%) were male. The overall mean age was 38.52 ±21.90 years (range; 5-90 years) with a median age of 37 years (IQR: 19-58). Refractive error 271(62.6%), cataract 69(15.9%) and diabetic retinopathy 37(8.5%) were the major causes of visual impairment, followed by amblyopia 15(3.5), corneal opacity 12(2.8), and glaucoma 8(1.8). Refractive errors, amblyopia, and corneal opacity were more common among those aged 5-20 years, while visual impairment caused by cataract, diabetic retinopathy and glaucoma was more common in older age groups. Conclusion: Refractive error was found to be the major cause among the participants with mild to severe visual impairment. Key Words: Visual impairment, Refractive error, Cataract, Diabetic retinopathy.